Egg morphology update based on new chorionic data of Potamanthus luteus (Linnaeus), Ephemera danica Müller and Oligoneuriella rhenana (Imhoff) (Insecta, Ephemeroptera) obtained by scanning electron microscopy - Ubero-Pascal, Nicolás; Puig, M. Angels (Zootaxa, 2007)
The chorionic patterns of Ephemeroptera eggs are very diverse and these have often been used for taxonomic and systematic purposes. In a great number of species, including Potamanthus luteus, Ephemera danica and Oligoneuriella rhenana, these egg features have been studied using light microscopy. However, current trends in egg morphology studies use scanning electron microscopy (SEM), so that the eggs of these species need to be re-described in order to establish morphological comparisons. The general chorionic features which have already been described in these three species are confirmed in our SEM study, although a more detailed description of both the architecture and arrangement of these can now be offered. In addition, this study has allowed us to note new morphological data, such as the chorionic reticulation in P. luteus and the complex extrachorion-adhesive layer in E. danica; classification of the lateral attachment structure in P. luteus and O. rhenana has been changed; and the variability of the polar cap observed in P. luteus underlines the care that must to be taken when selecting chorionic structures for taxonomic purposes.